2004
DOI: 10.1183/09031936.04.00009804
|View full text |Cite
|
Sign up to set email alerts
|

Morning levels of fibrinogen in children with sleep-disordered breathing

Abstract: Elevated fibrinogen level is a predictor of cardiovascular disease in adults, and it is associated with sleep-disordered breathing. Levels of fibrinogen in adults are affected by other co-existing cardiovascular risk factors, which are not usually present in children.To investigate the association between fibrinogen and sleep-disordered breathing, a case-control study was carried out in children with and without habitual snoring. All snoring children underwent polysomnography.Morning fibrinogen values in 30 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
10

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 53 publications
(74 reference statements)
0
26
0
10
Order By: Relevance
“…P-selectin, C-reactive protein, fibrinogen, interleukin-8, and interferon-␥ levels were found to be higher in children with snoring and/or OSA compared with control subjects. [387][388][389][390][391] In a study of 143 adolescents, mean C-reactive protein level demonstrated a dose-response increase with SDB that was independent of BMI and partially explained by the severity of nocturnal hypoxemia. 91 Whether these mediators predict cardiovascular risk in children and adolescents has yet to be demonstrated.…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%
“…P-selectin, C-reactive protein, fibrinogen, interleukin-8, and interferon-␥ levels were found to be higher in children with snoring and/or OSA compared with control subjects. [387][388][389][390][391] In a study of 143 adolescents, mean C-reactive protein level demonstrated a dose-response increase with SDB that was independent of BMI and partially explained by the severity of nocturnal hypoxemia. 91 Whether these mediators predict cardiovascular risk in children and adolescents has yet to be demonstrated.…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%
“…processes, may underlie such changes along with increasing the adherence of inflammatory mediators to endothelial cells and hypercoagulability [1,5,8,19,30,[39][40][41][42]. Hyperactivation and increased reactivity of the sympathetic system have been reported in children with OSA [43][44][45] and systemic blood pressure elevations are not only OSA-severity dependent [46][47][48], but are also associated with altered left ventricular geometry and contractibility [49].…”
Section: Sleep-related Disordersmentioning
confidence: 99%
“…Выявлено также, что у больных детей отмечается повышение плазменного уровня миелоидсвязанно-го белка 8/14 (MRP 8/14) -биомаркера воспаления сосудов, играющего важную роль в атеросклероти-ческом поражении сосудов [56]. Риск поражения со-судов усугубляется и повышением коагуляционного потенциала сыворотки на фоне обструктивных нару-шений дыхания во время сна у детей [57].…”
Section: российский вестник перинатологии и педиатрии 4 2016unclassified